The “added value” of enrolling hematological patients in clinical trials: a single-center experience - Loiacono, Stefano; Lucchini, Elisa; Rossetti, Maria Chiara; Palmieri, Clara; Cebulec, Irina; Provasi, Riccardo; Lena, Martina; De Bellis, Eleonora; Roni, Chiara; Zaja, Francesco (Frontiers in Hematology, 2025)
Pharmaceutical expenditure is constantly growing, in parallel with the increasing incidence of cancers and drug development costs. Enrolling patients in clinical trials provides countless advantages both for patients and the healthcare system; the pharmacoeconomic point of view is usually the least to be considered, but its magnitude should not be underestimated. The aim of this retrospective study was to estimate the pharmaceutical costs “avoided” by enrolling patients with hematological diseases in interventional clinical trials in a single institution. For each patient, the Standard-of-Care (SOC) therapy, which he or she would have received outside the clinical trial, was identified based on international guidelines, local clinical practice and Italy’s criteria for eligibility. The sum of the costs for SOC drugs represents the potential avoided pharmaceutical expenditure. In a 5-year period, 124 patients were enrolled in 37 interventional clinical trials. Thanks to an academic clinical trial several patients were treated with gemtuzumab ozogamicin, avoiding around €270.000 of SOC therapy. Enrolling patients with Non-Hodgkin’s Lymphoma generated a total avoided pharmaceutical expenditure of €254.546, with an average annual saving of more than €50.000, avoiding the costs of drugs such as polatuzumab vedotin (more than €70.000 enrolling 2 patients), intravenous and subcutaneous rituximab, liposomal doxorubicin, bendamustine and lenalidomide. Our analysis demonstrates how enrolling patients with hematological diseases in clinical trials can alleviate the burden on the Hematology Department pharmaceutical budget, avoiding SOC drug expenditure and securing grants, reimbursements, and payments not included in our analysis.